2022
DOI: 10.1002/der2.154
|View full text |Cite
|
Sign up to set email alerts
|

Micro injection of botulinum and its effects on the skin

Abstract: Introduction Microbotox generally refers to the injection of small aliquots of dilute botulinumtoxinA into the dermis or the junction of the dermis and underlying musculature. This novel procedure has been popularized as a treatment to improve skin quality. Objectives The purpose of this literature review is to further the understanding of techniques and to evaluate the published outcomes in microbotox treatment. Methods We conducted a keyword search in Pubmed, Google Scholar, and the university library databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This approach may contribute to the safety of BoNT-A injections as it has been shown that retrograde linear injections are superior in reducing forehead lines [ 50 , 51 ]. However, superficial hypodermic injections are safer, particularly in the lower part of the frontalis muscle [ 12 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach may contribute to the safety of BoNT-A injections as it has been shown that retrograde linear injections are superior in reducing forehead lines [ 50 , 51 ]. However, superficial hypodermic injections are safer, particularly in the lower part of the frontalis muscle [ 12 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%